Combined nutcracker syndrome and glomerulonephritis in pediatric patients: a single-center retrospective case series - So Hyun Ki; Min Hwa Son; Hyung Eun Yim (Kidney Research and Clinical Practice, 2024)
Background Nutcracker syndrome (NCS) has been reported to coexist with various glomerulonephritis (GN). This study investigated clinical features of NCS combined with GN in a pediatric case series and the possible relationship between these two conditions. Methods Clinical and pathologic findings of 15 children with NCS and biopsy-proven GN were analyzed. NCS was diagnosed with renal Doppler ultrasonography, abdominal computed tomography, and/or magnetic resonance imaging. Glomerular lesions were divided into two pathological categories: minor glomerular abnormalities (MGAs) and definite GN. Results Mean age of all patients was 11 ± 3.36 years and mean follow-up duration was 53.8 ± 29.3 months. Chief complaint was proteinuria with or without hematuria. During follow-up, five patients developed left kidney enlargement. Abnormal levels in immunological tests were revealed in 10 patients. Extrarenal symptoms including gonadal varicocele, splenic cyst, syncope, and anemia were found in seven patients. On kidney biopsy, seven patients had MGAs and eight children showed definite GN (one case of focal GN, one case of mesangial proliferative GN, one case of focal segmental glomerulosclerosis, two cases of immunoglobulin A [IgA] vasculitis nephritis, and three cases of IgA nephropathy). While the MGA group showed a higher proportion of isolated proteinuria and a lower estimated glomerular filtration rate (eGFR) at the last visit, there were no differences in age, clinical features of NCS, extrarenal symptoms, immunological tests, and eGFR decline rate between the two groups. Conclusion NCS may be associated with the presence of various GN. The causal relationship between NCS and GN should be further investigated.